The effect of alfalfa weevil control on alfalfa hay yield and quality - Ritter, B.; Bauernfeind, B. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 2-year-old, irriagated alfalfa field was left untreated or treated with ¼ lb, ½ lb, or 1 lb of Furadan® per acre on April 5, 1986. Alfalfa weevil populations were determined 2,9,16 and 23 days post-spraying. Forage samples were collected at about the 1/10 bloom stage of maturity. All three Furadan levels provided excellent weevil control up to 23 days post-spraying, and all resulted in an increase in dry matter yield. But only the yield of the 1 lb./A. treatment was significantly (P<.15) greater than the untreated forage (1.97 vs. 2.44 tons/A). There was no difference in nutrient composition between the untreated and treated forage. All Furadan treatment resulted in a net economic gain per acre. In this study, between ½ lb and 1 lb Furadan per acre resulted in the greatest weevil control and economic return per acre.
Keywords: Beef; Alfalfa; Weevil control; Yield; Quality